P18 Child maltreatment co-occurrence and associations with household dysfunction: evidence from the 1958 British birth cohort. (16th November 2010) - Denholm, R; Power, C; Thomas, C; Li, L
Abstract : Background: Child maltreatment has been associated with adverse health outcomes, including risk of mental health problems and cardiovascular disease. Little is known about how different forms of maltreatment co-occur and whether different patterns are associated with household dysfunction. Delineation of co-occurrence is important to establish in order that long-term health outcomes can be better identified and understood. Objective: To investigate (1) to what extent specific maltreatment subtypes co-occur in a British birth cohort and (2) how these patterns were associated with household dysfunction. Design: Longitudinal survey; the 1958 British birth cohort. Setting: England, Scotland and Wales. Participants: Individuals born during 1 week in March 1958. At age 45 y, 78% of the remaining cohort (11 971) completed questions on childhood experiences. Outcomes: Child maltreatment before age 16, including psychological, physical and sexual abuse and witnessing intimate partner violence, collected at age 45 y. Eleven indicators of parental neglectful behaviour, collected at 7, 11, 16 and 45 y, were aggregated to derive a cumulative neglect score. Information on household dysfunction (eg, parental mental health, alcohol/drug misuse, poverty) was collected during childhood and at 45 y. OR presented were adjusted for sex and social class at birth. Results: Psychological abuse (10.0%) was the most commonly reported maltreatment, followed by physical abuse (6.1%), witnessing abuse (6.0%) and sexual abuse (1.6%); 24% had a neglect score ≥3. 14% of participants experienced any one subtype of abuse. Of these, almost two thirds (64%) experienced further abuse subtypes and/or had a neglect score ≥3. Witnessing or experiencing abuse increased odds of reporting another maltreatment, for example, psychological and physical abuse OR 37.9 (95% CI 30.8 to 46.5). The odds of reporting any abuse increased with neglect score; for example, for sexual abuse OR ranged from 1.5 (0.9 to 2.6) to 4.5 (2.5 to 8.1). Common household dysfunction variables (eg, conflict and physical punishment) were strong predictors for all abuse subtypes. Other dysfunction measures most strongly associated with maltreatment differed, for example, odds of psychological abuse were increased in association with mother/father with nervous trouble (OR 4.7 (4.1 to 5.4), OR 4.1 (3.4 to 4.8), respectively); odds of neglect were increased for those in institutional care (OR 3.8 (2.7 to 5.4)) or with a family member in prison (OR 3.8 (3.0 to 4.8). Conclusion: Forms of maltreatment co-occurred in the cohort, such that cumulative exposure to neglect increased odds of abuse. Maltreated children had elevated exposure to household dysfunction.